Inter- and intra-plant variation in phenol content in grains of rice (Oriza sativa varieties using phenol colour reaction - KUMAR, SHAHIL; CHAKRABARTY, S K; RANJAN, RANJEET (The Indian Journal of Agricultural Sciences, 2021)
Different stages of phenol colour reaction showed induction of phenol colour reaction occur post anthesis, i.e. stage 2. In the later stages, i.e. stage 3 (dough) and 4 (harvest maturity) seeds showed similar phenol reaction with less intensity. Phenol content estimated at different stages of growth and maturity showed the highest at post fertilization stage, i.e. stage 2 and it decreased in stage third and fourth. Inter-panicle phenol content was not significantly different whereas intra-panicle difference in phenol content was observed.